Penyuluhan Pemberian Edukasi Fisioterapi Mengenai Hipertensi Pada Komunitas Lansia di Posyandu Mawar Balai RW 03 Kelurahan Dinoyo Kota Malang - Safira Friaviesta Maharani; Nurul Aini Rahmawati; Lina Sriyatun (Rena Cipta Mandiri, 2024)
Introduction: Hypertension, often referred to as the silent killer, is a major risk factor for mortality worldwide, including in Indonesia. It affects all age groups, with the elderly being the most vulnerable. Hypertension is defined as a condition where systolic blood pressure exceeds 140 mmHg and diastolic blood pressure exceeds 90 mmHg. It is categorized into primary hypertension, with an unknown cause, and secondary hypertension, caused by kidney, endocrine, heart, or adrenal disorders. Research Method: Educational counseling and sports therapy were conducted on October 19, 2024, from 08.30 to 10.00 WIB at Posyandu Mawar, Balai RW.03, Dinoyo Village, Lowokwaru District, involving 30 elderly respondents. Posters and leaflets were used as health promotion tools, along with a questionnaire containing four questions, each worth 25 points. Results: Pretest results indicated understanding of hypertension definition (70%), breathing exercises (45%), benefits (67.4%), and application (0%). Posttest results showed a 100% improvement in all components after the intervention. Conclusion: Counseling and exercise therapy significantly increased understanding and implementation of hypertension management among the 30 elderly respondents, reducing the risk of death, the severity of hypertension, and the likelihood of complications.